The demographic pattern of infection with chronic wasting disease in reindeer at an early epidemic stage. Issue 11 (1st November 2019) - Mysterud, Atle; Madslien, Knut; Viljugrein, Hildegunn; Vikøren, Turid; Andersen, Roy; Güere, Mariella Evelyn; Benestad, Sylvie L.; Hopp, Petter; Strand, Olav; Ytrehus, Bjørnar; Røed, Knut H.; Rolandsen, Christer M.; et al.
Abstract: Infection patterns linked to age and sex are crucial to predict the population dynamic effects of diseases in long‐lived species. How such demographic patterns of infection arise is often multifactorial, although the cause is commonly seen as a combination of immune status as well as variation in pathogen exposure. Prion diseases are particularly interesting, as they do not trigger an adaptive immune response; hence, differences in pathogen exposure linked to behavior could be the prime determinant of the pattern of infection. In cervids, the fatal prion disease, chronic wasting disease (CWD), is spreading geographically, with economic and cultural consequences in affected areas in North America, and all infected individuals eventually die from disease‐associated sequelae if they live long enough. Understanding the causes of the demographic pattern of infection with CWD is therefore urgent but is limited by the fact that reported data primarily come from related deer species in North America. The recent (detected 2016) emergence of CWD among wild alpine reindeer ( Rangifer tarandus ) in Norway with a different social organization, that is, no home range behavior and no matrilineal female groups, offers an opportunity to advance our understanding of how behavior influences the infection patterns. Testing of 1081 males and 1278 females detected 19 animals positive for abnormal prion protein in brain and/or lymphatic tissues. No calves and only one male yearling were infected, with the remaining positives being adults (representing 1.5% of adult males and 0.5% of adult females). We found a strong sex‐biased infection pattern in reindeer (with infection 2.7 times more likely in adult males), which is similar to the results reported in mule deer and white‐tailed deer. The hazard of being detected as positive increased with age in males. There was no close genetic relatedness among positive animals. The results were consistent with the within‐group contact of males being a possible major route of transmission. We discuss the demographic pattern of infection with CWD in view of the lack of stable home range behavior and other key behavioral traits of reindeer relevant to understanding pathogen exposure in general.